1997
DOI: 10.1152/jappl.1997.82.5.1397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical deformation on structure and function of polymorphonuclear leukocytes

Abstract: . Effect of mechanical deformation on structure and function of polymorphonuclear leukocytes. J. Appl. Physiol. 82(5): 1397-1405, 1997.-The present studies were designed to test the hypothesis that mechanical deformation of polymorphonuclear leukocytes (PMN) leads to functional changes that might influence their transit in the pulmonary capillaries. Human leukocytes were passed through 5-or 3-µm-pore polycarbonate filters under controlled conditions. Morphometric analysis showed that the majority of PMN were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
(56 reference statements)
6
28
0
Order By: Relevance
“…We confirmed this by assessing deformation after hydrostatic filtration through pores of defined size, which reorganizes and stabilizes the cytoskeleton (40). We found that unmanipulated PMNs forced through 8-pores, which are just larger than the cells, showed no morphologic effects of their passage through the filter, but cells pre-exposed to sphingomyelinase C displayed a prolate shape, showing they were larger than the pore and that they were unable to rapidly regain their shape after passage (data not shown).…”
Section: Ceramide Increases Surface ␤ 2 -Integrin Expression But Inhsupporting
confidence: 53%
“…We confirmed this by assessing deformation after hydrostatic filtration through pores of defined size, which reorganizes and stabilizes the cytoskeleton (40). We found that unmanipulated PMNs forced through 8-pores, which are just larger than the cells, showed no morphologic effects of their passage through the filter, but cells pre-exposed to sphingomyelinase C displayed a prolate shape, showing they were larger than the pore and that they were unable to rapidly regain their shape after passage (data not shown).…”
Section: Ceramide Increases Surface ␤ 2 -Integrin Expression But Inhsupporting
confidence: 53%
“…4 Decoupling the contributions of adhesion molecules and mechanical deformation is difficult. 12 Mechanical deformation alone, in the absence of any adhesion molecules, has been shown to cause pseudopod projection and stark changes in neutrophils biomechanical properties 27 while causing an increased adhesiveness by upregulating the integrins on the neutrophil surface. 12 Traditional methods for measuring the viscoelastic properties of materials require macroscopic samples and are thus incapable of providing localized rheological data for single cells.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mechanical deformation alone, in the absence of any adhesion molecules, has been shown to cause pseudopod projection and stark changes in neutrophils biomechanical properties 27 while causing an increased adhesiveness by upregulating the integrins on the neutrophil surface. 12 Traditional methods for measuring the viscoelastic properties of materials require macroscopic samples and are thus incapable of providing localized rheological data for single cells. Partial aspiration into micropipettes can be used to assess whole cell mechanical properties 7,28 using single cells as samples, but it does not provide localized information for different regions inside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…No cells were entrapped in the contralateral control microcirculation. Although physical entrapment may play a role in granulocyte sequestration (Hogg et al, 1992;Doerschuk et al, 1993;Wiggs et al, 1994;Kitagawa et al, 1997) and lymphokine-activated lymphocyte localization (Fisher et al, 1989) in the lung, lymphocyte entrapment does not appear to play a significant role in the delivery of lymphocytes to the oxazolone-stimulated skin.…”
Section: Discussionmentioning
confidence: 99%